Development and Psychometric Evaluation of the Computer-Aided Measure of Chinese Handwriting Legibility (CAM-CHL) for School-Age Children. - Huang, Wen-Feng; Wang, Tien-Ni; Chuang, Po-Ya; Chen, Hao-Ling (American Journal of Occupational Therapy)
Importance: Handwriting legibility is the main criterion for determining whether a child has handwriting difficulties. A comprehensive assessment of handwriting legibility with sound psychometrics is essential to timely identification of handwriting difficulties and outcome measurement after handwriting interventions. Objective: To evaluate the psychometrics of the Computer-Aided Measure of Chinese Handwriting Legibility (CAM-CHL) and to investigate Chinese handwriting legibility in school-age children using the CAM-CHL. Design: Cross-sectional, repeated observation, test–retest. Setting: Elementary schools in Taiwan. Participants: We recruited 25 lower-grade children for the examination of test–retest reliability, 75 children from all grade levels, and 10 senior schoolteachers for the examination of the CAM-CHL's convergent validity and the investigation of handwriting legibility. Outcomes and Measures: Children were asked to copy a set of Chinese characters as legibly as possible. We used the CAM-CHL to assess handwriting legibility in four domains: Size, Orientation, Position, and Deformation. The schoolteachers were asked to subjectively assess the handwriting legibility using a 3-point Likert-type scale. Results: The CAM-CHL demonstrated good to excellent test–retest reliability and acceptable random measurement error in all legibility domains. The CAM-CHL had fair to moderate convergent validity with schoolteachers' perceptions. Additionally, upper-grade children had better handwriting legibility in the Size and Position domains than lower-grade children. Conclusions and Relevance: The CAM-CHL, a comprehensive and objective method of assessing Chinese handwriting legibility, has sound reliability and acceptable validity, suggesting its potential as an outcome measure for school-age children. What This Article Adds: The CAM-CHL can be used in comprehensive evaluations of Chinese handwriting legibility in school-age children. The CAM-CHL has acceptable psychometrics for use as an outcome measure. This study supports the use of the Computer-Aided Measure of Chinese Handwriting Legibility (CAM-CHL) as an outcome measure with acceptable psychometrics for the comprehensive evaluation of the handwriting legibility of school-age children.